An Unusual Case of Teeth in Neck: An Interesting Case Report - Wadhwa, Vikram; Tandon, Swati; Singh, Maya; Bapat, Daamini (Indian Journal of Neurotrauma, 2024)
Foreign bodies of neck are a common occurrence after trauma and road traffic accidents. Foreign bodies can get lodged in the neck especially after open wound. These could range from a piece of glass, wood, pebble pieces, or the part of tool used for trauma. We report a case of an unusual foreign body in the neck. Posttrauma, patient had mandibular fracture with dislodgement of teeth in the neck masquerading as foreign body. Patient required surgical intervention for removal of teeth from the neck via an external incision and recovered uneventfully. The aim of the article was to highlight the importance of complete clinical and radiological examination in a patient of trauma. Missing teeth especially in cases of mandibular fracture must be searched for carefully.
Keywords: mandibular fracture; teeth in neck; facial fracture; displaced molars; foreign body neck